Optimalisasi Media Pembelajaran Pada Pengenalan Permainan Tradisional Indonesia “VINANES” - Noorlela Marcheta; Aulia Rieqy Firhan; Iwan Sonjaya (Journal on Education, 2023)
This study aims to create interactive learning media to optimize the introduction of traditional games called "VINANES" . These interactive multimedia is developt to make it easier for teachers to explain the material that contains information related to traditionals toys, animations, and games so that students are expected to be interested in learning the material presented and don't get bored during the learning process. Based on the results on 22 grade 3 elementary school students, it proves that the VINANES learning media is implemented very well, with a percentage of test results of 84.39%.